Groundwater contamination in Damaturu, Nigeria - Umara, B.; Yaji, M.; Fannami, A. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2004)
Groundwater quality was monitored in 10 wells in the proximity of solid and liquid waste disposal systems in Damaturu, Nigeria. In this study, nitrate, pH, electrical conductivity, turbidity, total dissolved solids, hardness, colour, iron, chloride, sulphate, fluoride and coliform count were examined in the laboratory using standard procedures. Closeness to pit latrines and septic tank resulted in significant concentrations of nitrate (28, 40 and 41 mgl-1 in wells 2, 8 and 9 respectively) which exceed the European Community Standards. Consumption of water with high nitrates above the permissible limit of 20 mgl-1 can cause methyglobenemia syndrome. Co-existence with waste disposal system resulted in high pH, iron and faecal contamination with average coliform density of 29 (100ml)-1 of sample exceeding the maximum permissible limit. Total coliform indicate pathogens that cause cholera, typhoid, dysentery, gastro-enteritis, diarrhea and so on. Excessive iron can impart colour and stimulate bacterial growth. The pH values normally exert influence on biological activity and may result in undesirable taste. The paper tries to offer some suggestions to the identified problems.